UPAYA PENINGKATAN LITERASI MEMBACA DENGAN PENGADAAN POJOK BACA DAN BIMBINGAN BELAJAR PADA SISWA SEKOLAH DASAR DI UPTD SDI WAEWARU - Maria Yasinta Baka; Marselina Yolanda Bupu; Dimas Qondias (Asosiasi Dosen Muda Indonesia, 2024)
The aim of this research is to increase student literacy by providing a reading corner and tutoring at UPTD SDI Waewaru. The research method used is descriptive qualitative, with data collection techniques in the form of observation, interviews and documentation. The subjects of this research were 18 class IV UPTD SDI Waewaru students. This research went through several stages, namely planning, implementation and observation. The research results after implementing the reading corner showed that out of 18 students there were 13 students or 72% of students could read fluently. This shows that the provision of reading corners and tutoring has a positive impact on students' interest and literacy skills, especially in terms of reading and writing. Thus, this strategy is effective in increasing literacy in the school environment.